Assessing the Impact of Institutions on Social Development - Ionut Jianu; Maria-Daniela Tudorache; Constantin-Stefan Simion (19th International Conference on Business Excellence. Proceedings, 2025)
This paper examines the impact of institutions on income inequality in 27 European Union member states over the period 2011-2022, using the method Panel Estimated Generalized Least Squares. To catch the quality of institutions we used World Governance Indicators published by World Bank, especially those related to rule of law and political stability and absence of violence/terrorism. The results confirmed a negative relationship between institutional quality (rule of law, political stability and absence of violence/terrorism) and income inequality, indicating that the quality of the rules driving human action really matter and influences the dynamic of social development. In addition, we used additional variables to improve the quality of the model, by using variables related to labour market, education and household sectors. In this respect, we found a positive association between income inequality and other explanatory factors, such as school dropout, unemployment rate and the housing cost overburden rate. Even if the model is limited to five income inequality drivers, we have demonstrated that the calculated coefficients are not affected by multicollinearity or other model issues. In this respect, the estimation provides high confidence results, which can be fully taken into consideration by governments, when drafting policy measures oriented to tackle income inequality.
Keywords: E02; D63; C33; 330; income inequality; rule of law; political stability; institutions; early leavers